Telling the Christian story differently : counter-narratives from Nag Hammadi and beyond - Parkhouse, Sarah; Watson, Francis, 1956- (London ; T&T Clark, 2020)
"This volume is devoted to the 'counter-readings' of the core Christian story proposed by texts from Nag Hammadi and elsewhere. Its chapters retrace the major elements of the Christian story in sequence, showing how and why each of them was disputed on inner-Christian grounds and reflecting on the different accounts of Christian identity underlying these disputes. Contributors present material that is often difficult and little-known to contribute to ongoing efforts to integrate Nag Hammadi and related literature into the mainstream of New Testament and early Christian studies"--
Introduction / Francis Watson, Durham University, UK and Sarah Parkhouse, Australian Catholic University, Australia -- Chapter 1: The Curse of the Creator: Galatians 3.13 and Negative Demiurgy / M. David Litwa, Australian Catholic University, Australia -- Chapter 2: The Hypostasis of the Archons and Re-imagining Genesis / Mark Goodacre, Duke University, USA -- Chapter 3: Jesus versus the Lawgiver: Narratives of Apostasy and Conversion / Francis Watson, Durham University, UK -- Chapter 4: Why are the Disciples 'Like the Angels' Redemption Through Sin in the Gospel of Judas / Jonathan Cahana, Hebrew University of Jerusalem, Israel -- Chapter 5: 'Surely These are Heterodox Teachings': The Gospel of Mary and Tertullian in Dialogue / Sarah Parkhouse, Australian Catholic University, Australia -- Chapter 6: Attempting the Impossible? Ptolemy's Letter to Flora as Counter-Narrative / Joseph Verheyden, Katholieke Universiteit Leuven (KU Leuven), Belgium -- Chapter 7: Counter-Narratives or Competing Voices? Early Christians and the Resurrection of the Flesh / Outi Lehtipuu, University of Helsinki, Finland -- Chapter 8: Resurrection in the Exegesis on the Soul (NHC II,6) / Kimberly A. Fowler, Durham University, UK -- Chapter 9: Losing the Plot: Irenaeus, Biblical Narrative, and the Rule of Truth / Devin L. White, Australian Catholic University, Australia -- Bibliography -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Jesus Christ; Jesus Christ -- History of doctrines -- Early church, ca. 30-600.; Biblical studies & exegesis; Electronic books